Analisa dan Perancangan Sistem Informasi Perpustakaan Menggunakan Metode Waterfall : Studi Kasus: SMK Yapermas Jakarta - Devara Putri; Ahmad Taufik (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
The development of information technology in the digital era has significantly impacted various sectors, including libraries in educational institutions. This study focuses on the analysis and design of a web-based library information system at SMK Yapermas Jakarta, utilizing the Waterfall software development methodology. The Waterfall model was chosen for its systematic structure, ranging from requirements analysis to system maintenance. Currently, the library management at SMK Yapermas is still manual, leading to several issues such as slow book searching, borrowing, returning processes, and potential data errors. The objective of this study is to design a system that enhances library service efficiency. The research findings indicate that the web-based system significantly improves the efficiency and quality of services, with excellent ratings in various development stages, such as requirement analysis (81% - 88%) and system testing (81% - 86%). Therefore, the web-based library is expected to provide a more effective solution for library management at SMK Yapermas Jakarta and other schools.